STUDI LITERASI PENGEMBANGAN MANAJEMEN KLUB SEPAKBOLA DI INDONESIA - Andrew, Richard; Suryawan, Ian Nurpatria (Modus Journals, 2015)
Abstract Football is the most popular sport in the World and in Indonesia. However, it seems that at the moment many difculties and challenges occur in Indonesian sport industry that impede the development. Another problem that become serious issue is the dispute between Indonesian Football Association with the Indonesian Ministry of Youth and Sports. The issue grows since there was an organizational problem within Indonesian League clubs from Surabaya and Malang East Java Indonesia. Based on some similar event abroad, those kinds of issues should be resolved with an integrated management system within Indonesian Football Club. The main purpose of this literacy study is to improve the quality of football club management in Indonesian Football Clubs as an alternative to the development of tourism in Indonesia.Keywords: Football, Management, PSSI, Tourism.